2013
DOI: 10.5812/jjnpp.6783
|View full text |Cite
|
Sign up to set email alerts
|

The Organochlorine Pesticides Residue Levels in Karun River Water

Abstract: Background:The organochlorine pesticides (OCPs) are among the most commonly used in water streams around the world. Most of these contaminants are highly hydrophobic and persist in sediments of rivers and lakes. Studies have suggested that OCPs may affect the normal function of the human and wildlife endocrine systems. Objectives: The aim of this study is to determine the concentrations of selected organochlorine pesticides residues [OP'DDT, PP'DDT, alderin, dieldrin, heptachlor, (α,ß,γ,δ) HCH, (α, ß) endosulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Organochlorine pesticides (OCPs) are a well-known group of persistent man-made chemicals that are extremely harmful to humans and wildlife (Pirard et al 2018;Li et al 2018;Behfar et al 2013). Their accumulation in the environment, especially in soils, can cause significant stress on ecosystems (Artikov et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organochlorine pesticides (OCPs) are a well-known group of persistent man-made chemicals that are extremely harmful to humans and wildlife (Pirard et al 2018;Li et al 2018;Behfar et al 2013). Their accumulation in the environment, especially in soils, can cause significant stress on ecosystems (Artikov et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many industries such as paper and pulp manufacturing, metallurgical industries, and cane factories are located on the plain (Ahmadi et al 2019). It should be noted that OCPs are still used in Iran (Shahmoradi et al 2019) and Behfar et al (2013) reported different OCP levels along the Karun river in Khuzestan province (22.25-89.34 µg/L). In addition, previous investigations have demonstrated OCPs in agricultural products and food (Amrollahi et al 2018;Amirahmadi et al 2013), dairy products (Ashnagar et al 2009;Koohi et al 2011;Bayat et al 2011), fish (Ebadi et al 2006;Kafilzadeh 2015;Seifzadeh et al 2018), sturgeon (Kajiwara et al 2003), and human breast milk (Behrooz et al 2009a;Shahmoradi et al 2019;Cok et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…But the area under the curve of bare GCE and MWCNT coated GCE are nearly the same: the values are 1.08 × 10 À 3 C and 1.14 × 10 À 3 C, respectively. The electrochemical oxidation of AA oxidation on MWCNT is probably different from that of the bare GCE [66][67][68]. AA oxidation on MWCNT coated electrode is a two-step one-electron transfer oppose to direct single-step two-electron transfer at bare GCE.…”
Section: Full Papermentioning
confidence: 93%
“…Pesticides are commonly used both in domestic and agricultural production to provide crop protection, boost up the yield in agricultural productivity, improve nutrition in food, its use is assumed an economic, labour-saving, and efficient tool for pest management, despite its adverse effects on ecological environment, human and animal's health [1,2]. Their widespread use combined with over-application, accidental spills, runoff from mixing-loading areas, and faulty waste disposal creates environmental concerns as well as toxic biological [3]. In 1990 when the use of pesticide was not as much in Jos -Plateau as in recent years, [4] stated that an approximately three million people are poisoned and 220,000 die each year around the world from insecticide poisoning, the majority of which occur in developing countries, although far greater quantities are used in developed countries [5] Pesticides have been associated with a wide variety of human health hazards, ranging from acute impacts such as headache, vomiting, and diarrhoea to chronic impacts like cancer, reproductive harm, and endocrine disruption [6,7].…”
Section: Introductionmentioning
confidence: 99%